Stretch‐shortening cycle muscle power in women and men aged 18–81 years: Influence of age and gender. Issue 4 (28th March 2013) - Edwén, C. E.; Thorlund, J. B.; Magnusson, S. P.; Slinde, F.; Svantesson, U.; Hulthén, L.; Aagaard, P.
<x xml:space="preserve">Abstract</x> This study explored the age‐related deterioration in stretch‐shortening cycle (SSC) muscle power and concurrent force–velocity properties in women and men across the adult life span. A total of 315 participants (women: n = 188; men: n = 127) aged 18–81 years performed maximal countermovement jumps on an instrumented force plate. Maximal SSC leg extension power expressed per kg body mass (Ppeak) was greater in men than in women across the adult age span (P < 0.001); however, this gender difference was progressively reduced with increasing age, because men showed an ∼50% faster rate of decline in SSC power than women (P < 0.001). Velocity at peak power (VPpeak) was greater in men than in women (P < 0.001) but declined at a greater rate in men than in women (P = 0.002). Vertical ground reaction force at peak power (FPpeak) was higher in men than in women in younger adults only (P < 0.001) and the age‐related decline was steeper in men than in women (P < 0.001). Men demonstrated a steeper rate of decline in Ppeak than women with progressive aging. This novel finding emerged as a result of greater age‐related losses in men for both force and velocity. Consequently, maximal SSC power production was observed to converge between genders when approaching old age.